2002
DOI: 10.1248/cpb.50.583
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Constituents from the Aerial Part of Baccharis dracunculifolia DC. II.

Abstract: In the course of our research on the constituents of Brazilian plants, we started investigation of the glycosides from Baccharis dracunculifolia DC. (Compositae); we previously reported the structures of dracunculifosides A-J from the aerial part of this plant.1) Recently, ten new glycosides were isolated along with five known compounds identified by their NMR spectral data [1: 3,4-O-dicaffeoylquinic acid methyl ester, 2) 2:]. This paper also describes the isolation and structural elucidation of these new comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The 13 C and 1 H NMR spectra showed the presence of a β-glucopyranosyl moiety, two feruloyl moieties, two 1,3,4,5-tetrasubstituted symmetrical benzene signals (δ 6.67, 2H), two oxygenated methylene signals at δ 4.20 (2H, dd, J ) 9.4, 3.4 Hz), 3.84 (2H, overlapping), and four methine signals including two oxygen-bearing methines [δ 4.66 (2H, d, J ) 3.4 Hz, H-7,-7′), 2.99 (2H, m, H-8,-8′)], along with six methoxy signals at δ 3.81 (6H, s) and 3.80 (6H, s) (see Table 1). By comparison of the above 1 H NMR data with those of syringaresinol-O-β-glucopyranoside (15), compound 4 was determined to be a derivative of syringaresinol-O-β-glucopyranoside with two additional feruloyl moieties. Mild alkaline hydrolysis of compound 4 produced {[R] D 27 ) -26.3 (c ) 0.24, MeOH)}, which was identified as syringaresinol-O-β-D-glucopyranoside.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C and 1 H NMR spectra showed the presence of a β-glucopyranosyl moiety, two feruloyl moieties, two 1,3,4,5-tetrasubstituted symmetrical benzene signals (δ 6.67, 2H), two oxygenated methylene signals at δ 4.20 (2H, dd, J ) 9.4, 3.4 Hz), 3.84 (2H, overlapping), and four methine signals including two oxygen-bearing methines [δ 4.66 (2H, d, J ) 3.4 Hz, H-7,-7′), 2.99 (2H, m, H-8,-8′)], along with six methoxy signals at δ 3.81 (6H, s) and 3.80 (6H, s) (see Table 1). By comparison of the above 1 H NMR data with those of syringaresinol-O-β-glucopyranoside (15), compound 4 was determined to be a derivative of syringaresinol-O-β-glucopyranoside with two additional feruloyl moieties. Mild alkaline hydrolysis of compound 4 produced {[R] D 27 ) -26.3 (c ) 0.24, MeOH)}, which was identified as syringaresinol-O-β-D-glucopyranoside.…”
Section: Resultsmentioning
confidence: 99%
“…After partition procedures and TLC, NMR, and HPLC analyses of obtained organic phases, the presence of non-glycosylated flavonoid and triterpenes in the CH 2 Cl 2 phase and phenolic derivatives in the EtOAc phase was suggested. These phases were subjected to several chromatographic steps and NMR spectroscopic analysis to afford a mixture of oleanolic+ursolic acids (Seebacher et al 2003) and pure pectolinaringenin (Hase et al 1995) from CH 2 Cl 2 phase as well as pure caffeic and ferulic acids (Nagatani et al 2002) from EtOAc phase.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…There are few studies showing the occurrence of compounds of this class in Asteraceae species, such as the work from Gao et al [40], Ragasa et al [41], and Nagatani et al [42], which have reported monoterpene glycosides from Hymenoxys ivesiana , Erigeron linifolius , and B. dracunculifolia . In the literature, some studies have described the presence of 2-hydroxy-isoforone in plants but never as a nor-monoterpene glycoside; this unusual class of compound has been previously reported only twice (ranthenone glucoside and officinoterpenoside D) [33, 34].…”
Section: Discussionmentioning
confidence: 99%